2020
DOI: 10.1073/pnas.2001778117
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Kondo lattice electronic structure above the transport coherence temperature

Abstract: The temperature-dependent evolution of the Kondo lattice is a long-standing topic of theoretical and experimental investigation and yet it lacks a truly microscopic description of the relation of the basic f-c hybridization processes to the fundamental temperature scales of Kondo screening and Fermi-liquid lattice coherence. Here, the temperature dependence of f-c hybridized band dispersions and Fermi-energy f spectral weight in the Kondo lattice system CeCoIn5 is investigated using f-resonant angle-resolved p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
43
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 52 publications
13
43
1
Order By: Relevance
“…This is consistent with T hyb 0 ≈ 160K in this compound, see Table I. High-resolution ARPES results on CeCoIn 5 that are largely compatible with those of Chen et al (Chen et al, 2017) have also been reported by Jang et al (Jang et al, 2017). Though ARPES measurements on heavy-electron compounds have been a major experimental achievement, care has to be taken when extrapolating to the hightemperature region where the 4f electrons have to be localized across the phase diagram, as argued above.…”
Section: B Cecoin5supporting
confidence: 91%
“…This is consistent with T hyb 0 ≈ 160K in this compound, see Table I. High-resolution ARPES results on CeCoIn 5 that are largely compatible with those of Chen et al (Chen et al, 2017) have also been reported by Jang et al (Jang et al, 2017). Though ARPES measurements on heavy-electron compounds have been a major experimental achievement, care has to be taken when extrapolating to the hightemperature region where the 4f electrons have to be localized across the phase diagram, as argued above.…”
Section: B Cecoin5supporting
confidence: 91%
“…This is consistent with the onset of c − f hybridization at high temperature obtained from a recent ultrafast optical pump-probe measurement [26]. This behavior is also similar to other HF compounds, e.g., CeCoIn 5 [27,28], and it could be attributed to Kondo screening involving CEF excitations [27][28][29][30]. Analysis of the magnetic susceptibility and inelastic neutron scattering suggests that the first excited CEF doublet in CeRh 6 Ge 4 lies at ∼6 meV above the ground-state doublet and it hybridizes strongly with the conduction bands [31].…”
supporting
confidence: 91%
“…The uncertainty of V is ∼ AE 10 meV along k y and slightly larger along k x due to weaker bands with smaller bending. Another source of uncertainty in the estimation of V is related to the RC-FDD division: since the ARPES energy resolution (∼20 meV) is larger than 4k B T, the recovered 4f bands above E F could be pushed slightly above the real positions [28], resulting in possible inaccuracy in V. However, since V along k y is much larger than the possible energy shift, this complication should not affect our main conclusion: V is obviously larger along k y compared to along k x . Such an anisotropic V is also manifested in the raw data via the presence The momentum anisotropy in V can be attributed to the crystal structure: the c − f hybridization should be dominated by electronic couplings between Ce and 12 nearest neighbor Rh and Ge atoms, which form small hexagons in the a − b plane halfway between Ce atoms along the chains.…”
mentioning
confidence: 99%
“…One way to view f-electron delocalization is as a result of Kondo hybridization between the f level and conduction electrons. Although there are reports of hybridization developing below about 45 Kelvin in pure CeCoIn5 (27) and Cd-doped Ce-CoIn5 (32) resulting in a detectable f-electron contribution to the Fermi surface, we find that the low-temperature carrier density of these materials is consistent with predominantly localized f-electrons (Fig. 1).…”
contrasting
confidence: 50%